International Symposium on Code Generation and Optimization, 2004. CGO 2004.
DOI: 10.1109/cgo.2004.1281675
|View full text |Cite
|
Sign up to set email alerts
|

FLASH: foresighted latency-aware scheduling heuristic for processors with customized datapaths

et al.

Abstract: Application-specific instruction set processors (ASIPs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In the past, there have been several studies to use only selected forwarding paths such that impact on performance is minimal [Fan et al 2003;Shrivastava et al 2005], and compiler techniques were suggested to further minimize the impact on performance [Park et al 2006;Kudlur et al 2004]. As less frequently used paths are not present in the limited bypass case, there will be minimal effect on RF energy savings achieved due to our proposed architecture.…”
Section: Previous Workmentioning
confidence: 96%
“…In the past, there have been several studies to use only selected forwarding paths such that impact on performance is minimal [Fan et al 2003;Shrivastava et al 2005], and compiler techniques were suggested to further minimize the impact on performance [Park et al 2006;Kudlur et al 2004]. As less frequently used paths are not present in the limited bypass case, there will be minimal effect on RF energy savings achieved due to our proposed architecture.…”
Section: Previous Workmentioning
confidence: 96%
“…However, this is generally done in the context of a single-issue architecture, thus there is no significant scheduling component. A related area is scheduling to processors with partial register bypass networks [11,23]. Partial bypass introduces the problem of variable latencies on dataflow edges depending on function units chosen for a producer/consumer pair.…”
Section: Related Workmentioning
confidence: 99%